HUBUNGAN KONDISI FISIK RUMAH DENGAN KEJADIAN PENYAKIT TUBERKULOSIS PARU DI WILAYAH KERJA PUSKESMAS SIGOMPUL KEC. LINTONGNIHUTA KAB. HUMBANG HASUNDUTAN TAHUN 2018 - Fithri Handayani Lubis; Syska Simamora `Syska (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2019)
Tuberculosis is the old disease that is now one of the biggest in the health sector. The factor of related to the incedence of tuberculosis are ventilation, type of floor, lighting, humidity. The purpose of this study is to find out the relationship between the physical condition of the house and the incidence of pulmonary tuberculosis in the Sigompul Community Health Center Work area Kecamatan Lintongnihuta Kabupaten Humbang Hasundutan. The method research uses Analitycal Observational design with Cross sectional approach. The subject of this study were respondent of Pulmonary Tuberculosis from October to January 2019 with a population of 85 peoples. The sample selection with sistematic random sampling produce of sample 40 peoples. The data collection methods use observation sheets and data analysis using the chi- square test. The results of the study indicate that there is a relationship between ventilatio (p=0,006), type of floor (p=0,039), lighting(p=0,034) and humidity (p=0,013) with the incidence of pulmonary tuberculosis. For the community, it is expected to create a safe home environment for family, celan and healthy lifestyle. For Sigompul Health Center is expected to implement health program that have been implemented by the goverment in recuding the incidence of pulmonary tuberculosis.